Changes in Biomodels in Response to Recombinant Protective Anthrax Antigen Inoculation - P. Yu. Popova; S. A. Bugorkova; N. I. Mikshis; A. P. Semakova; Yu. A. Popov; T. N. Shchukovskaya (Проблемы особо опасных инфекций, 2013)
one. The data obtained has substantiated the lack of an expressed damaging effect of the recombinant protective antigen on the cells and tissues of the macroorganism, as well as possibility of its application as one of the core components of the chemical anthrax vaccine.